2023
DOI: 10.1186/s12889-022-14501-1
|View full text |Cite
|
Sign up to set email alerts
|

The association between healthy beverage index and quality of life among overweight and obese women: a cross-sectional study

Abstract: Background Although several studies have evaluated the association between patterns of beverage consumption with different components of quality of life separately, the findings are controversial. In addition, none have examined all components of quality of life together in relation to patterns of beverage consumption. Therefore, this study was conducted to identify the association between healthy beverage index (HBI) and quality of life among overweight and obese women. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The results of the present study are in line with Vancampfort et al [53], who reported that QoL can be particularly poorer in women with BED compared to men with BED. According to Castanha et al (2018), the effects of obesity impact an individual's quality of life (QoL), whose indicators are characterized by lower social interaction, low self-esteem, social isolation, stress, and mental illnesses [45,47,48]. Appolinario et al [51], Giel et al [10], Singleton et al [52], and Vancampfort et al [53] also mentioned that individuals with BED experience more comorbid mental health problems, more specifically, depression [49] and anxiety disorders [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study are in line with Vancampfort et al [53], who reported that QoL can be particularly poorer in women with BED compared to men with BED. According to Castanha et al (2018), the effects of obesity impact an individual's quality of life (QoL), whose indicators are characterized by lower social interaction, low self-esteem, social isolation, stress, and mental illnesses [45,47,48]. Appolinario et al [51], Giel et al [10], Singleton et al [52], and Vancampfort et al [53] also mentioned that individuals with BED experience more comorbid mental health problems, more specifically, depression [49] and anxiety disorders [50].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, an association between QoL and its components in women with overweight and obesity was found. It seems that overweight women, in comparison to NW individuals, tend to express a lower QoL [47]. Chu et al [48] found differences, similarly, in the QoL between women with and without obesity.…”
Section: Introductionmentioning
confidence: 96%
“…(3) The research results of Niloufar Rasaei et al on the cholesterol/Saturated fat acid index CSI and sleep quality of overweight and obese women in 2023 show that people with higher CSI units are more likely to have sleep problems. (4) We can see that high cholesterol levels have a certain impact on the sleep of different people, causing insomnia, sleep apnea syndrome and other diseases, while sleep disorder will induce the risk of high cholesterol, causing Atherosclerosis and other diseases, seriously affecting people’s health. Therefore, we chose the special population of high cholesterol patients as the research object.…”
Section: Research Backgroundmentioning
confidence: 99%
“…One of the main contributors to global non-communicable diseases and mortality is the rising incidence of obesity 1 3 . Estimates suggest that by 2030, one billion people worldwide, comprising one in seven males and one in five females, will be affected by obesity 4 .…”
Section: Introductionmentioning
confidence: 99%